Normalization of the Input Signal During Speech Signal Preprocessing - A.A. Rakhmanov (Research Parks Publishing LLC, 2022)
It is important to pre-process and normalize a voice signal before recognizing and processing it. Since there are a variety of variables that might affect the sound signal's amplitude when recording speech, including the speaker's voice volume, proximity to the microphone, type of recording equipment, etc. In this post, we'll look at the input signal normalization technique and its first processing in preparation for building a model and an algorithm for identifying audio signals.